Irradiation-induced hardening in fusion relevant tungsten grades with different initial microstructures. (7th September 2021) - Chang, ChihCheng; Terentyev, Dmitry; Zinovev, Aleksandr; Van Renterghem, Wouter; Yin, Chao; Verleysen, Patricia; Pardoen, Thomas; Vilémová, Monika; Matějíček, Jiri
Abstract: The development of advanced tungsten grades able to tolerate irradiation damage combined with thermo-mechanical loads is important for design of plasma-facing components for DEMO. The material microstructure (i.e. grain size, dislocation density, sub grains, texture) is defined by manufacturing and post heat treatment processes. In turn, the initial microstructure might have an important influence on the accumulation of neutron damage because irradiation defects interact with microstructural defects evolving into a new microstructural state. In this work, the microstructure and hardness of four tungsten grades is assessed before and after neutron irradiation performed at 600, 1000 and 1200 °C, up to a dose of ∼1.2 dpa. Experimental characterization involves hardness testing, energy dispersive spectroscopy, electron backscatter diffraction, and transmission electron microscopy. The investigated grades include Plansee and AT&M ITER specification tungsten, as well as fine grain tungsten produced by spark plasma sintering, and ultra-fine grain tungsten reinforced with 0.5 wt% ZrC particles.